Analisis Teknik-Teknik Kriptografi Terhadap Serangan Jaringan Local - Ragil Aria Dewanto; Aries Suharso (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to find out whether a poor network topology can be a important aspect of data leakage if someone wants to steal data without the permission of an institution. The research methodology used in this study is quantitative methods and cryptographic techniques, wherein the quantitative method there are several specifications, namely structured, planned, and systematic, by performing analysis, substitution, blocking, permutation, expansion, and compression. The topology is divided into several types, namely ring topology, star topology, bus topology, tree topology, and mesh topology. In-network attacks that usually occur are spoofing, in-the-middle-attack, and sniffing. The results show that designing a local network topology using several types of topologies can make the network structure more secure. The results also show that combining a star topology and a tree topology makes the local network more secure. The results also show that combining cryptographic techniques can prevent network attacks that have been studied, especially combining blocking and permutation cryptography techniques.